Upaya Petani Meningkatkan Pendapatan di Desa Ampera Kecamatan Palolo Kabupaten Sigi (Studi Kasus Petani Kakao) - Utami Fatya, Dizha; Nurvita (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
This research was conducted in Ampera Village, Palolo District, Sigi Regency. The purpose of this study is to explain what factors cause the low income of cocoa farmers to increase their income in Ampera Village, Palolo District, Sigi Regency. This research is a qualitative research using a descriptive approach. The subjects of this study were Cocoa Farmers, totaling eight people and selected by Snowball Sampling. Data was collected by means of observation, documentation, and interviews. The resulting data were analyzed by data reduction, data presentation, and drawing conclusions. The results showed (1) there were two factors that resulted in the low income of farmers, namely productivity factors consisting of (age of cocoa plants, soil type, soil fertility, and land area) and garden maintenance factors consisting of (fertilization, cacao plant spacing, adequacy of labor, and pruning). (2) the efforts of cocoa farmers in Ampera Village in increasing income are very good, the government always provides counseling on the latest techniques in caring for cocoa plants so that they can produce good and quality cocoa pods.